Carpentry & joinery - Brett, Peter, 1950- (Cheltenham : Nelson Thornes, 2005)
Book 1 provides theoretical knowledge and a foundation in carpentry and joinery. This work includes the latest construction techniques with up-to-date illustrations and photographs. It provides a unique approac h to NVQ by dividing theory and practice into two books. It is fully up dated to cover recent legislation and the latest NVQ specifications. It is an ideal resource for carpentry and joinery students as well as pra ctising carpentry and joinery workers.
Bk. 1. Job knowledge -- bk. 2. Practical activities.
Includes index
Keywords: Carpentry; Joinery